DEFB1 polymorphisms and salivary hBD-1 concentration in Oral Lichen Planus patients and healthy subjects. (January 2017) - Polesello, Vania; Zupin, Luisa; Di Lenarda, Roberto; Biasotto, Matteo; Pozzato, Gabriele; Ottaviani, Giulia; Gobbo, Margherita; Crovella, Sergio; Segat, Ludovica
Highlights: DEFB1 5′UTR polymorphisms were genotyped in Italian healthy subjects and Oral Lichen Planus (OLP) patients. HBD-1 salivary concentration was measured and was significanlty different in Italian healthy subjects and OLP patients. DEFB1 − genotypes were correlated with the hBD-1 salivary concentration. The −52 G > A SNP correlated with hBD-1 salivary concentration in both healthy subjects and OLP patients. The −44C > G SNP correlated with hBD-1 salivary concentration in OLP patients. Abstract: Objectives: The aetiology of Oral Lichen Planus (OLP), a chronic inflammatory disease of oral mucosa, is not yet well understood. Since innate immunity may be hypothesized as involved in the susceptibility to OLP, we studied human beta defensin 1 (hBD-1) an antimicrobial peptide constitutively expressed in the saliva, looking at functional genetic variants possibly able to diminish hBD-1 production an consequently conferring major susceptibility to OLP. Design: We analysed three DEFB1 polymorphisms at 5′ UTR, −52G > A (rs1799946), −44C > G (rs1800972), −20G > A (rs11362) and two DEFB1 polymorphisms at 3′UTR, c*5G > A (rs1047031), c*87A > G (rs1800971), with the aim of correlating these genetic variants and hBD-1 salivary level in a group of OLP patients and in healthy subjects. We also evaluated hBD-1 salivary concentrations, using ELISA, in OLP and healthy controls. Results: We compared hBD-1 concentrations in OLP and healthy subjects: hBD-1 concentration was significantly higher in OLP patients respect to control. When considering the correlation between DEFB1 polymorphisms genotypes and hBD-1 expression levels, significant results were obtained for SNPs −52G > A (p = 0.03 both in OLP patients and healthy individuals) and −44C > G (p = 0.02 in OLP patients). Conclusions: hBD-1 production was different between OLP and healthy subjects (not age-matched with OLP). DEFB1 gene polymorphisms, −52G > A and −44C > G, correlated with hBD-1 salivary concentrations.